A Study to Assess Effectiveness of Nurse Lead Program for Implementation Of Invitro Fertilization Treatment & Related Coping Strategies Among Infertile Women at Akanksha Hospital Anand, Gujarat - Agnihotri , Rashmi (Journal of Neonatal Surgery, 2025)
This study evaluates the effectiveness of a nurse-led program in enhancing knowledge and promoting coping strategies among infertile women undergoing In-Vitro Fertilization (IVF) treatment at Akanksha Hospital in Anand, Gujarat. Using a pre-experimental research design, 444 infertile women were selected through convenient sampling. The study assessed participants' knowledge of infertility, treatments, and psychological reactions, as well as the efficacy of a nurse-led training program aimed at improving understanding and coping mechanisms. The findings revealed that while respondents had a good understanding of IVF complications and treatment modalities, there were gaps in knowledge regarding the primary causes of infertility. The study also highlighted the importance of individualized mental health support, given the variety of coping strategies employed by respondents. The nurse-led program received positive feedback, with 86.7% of respondents indicating that it adequately addressed their needs. The study concludes that managing infertility requires comprehensive knowledge, psychological support, and specialized educational programs. The results underscore the value of targeted educational initiatives and nurse-led programs in raising awareness and providing support to infertile women.